DGI-005 Analysis of Levofloxacin Use in Geriatric Units at a University Hospital. (12th March 2013) - Lebaudy, C; Chautant, F; Bourgeois, I; Boye, F; Gerard, S; Vellas, B; Cestac, P
Abstract : Background: Overuse of antibiotics, such as fluoroquinolones and third-generation cephalosporins, is a major cause of the emergence of extended-spectrum beta lactamase producing enterobacteriaceae. The use of levofloxacin in elderly inpatients is widespread. Purpose: We investigated the conditions in which this drug was prescribed. Materials and Methods: From 1st January to 31st March 2012, information was recorded on every new levofloxacin prescription from the geriatric units: indication, dose, duration, patient's medical history, renal function and previous antibiotic. In parallel, levofloxacin consumption was assessed and expressed in terms of the number of Defined Daily Doses (DDD) per 1000 patient-days (PD). The consumption was compared with the data from the French antibiotic network "RAISIN". Results: 87 patients had a levofloxacin prescription: 55% for community-acquired pneumonia, 20% for nursing-associated pneumonia, 16% for nosocomial pneumonia, and 9% for others indications. 77% of the patients had previously received another antibiotic (47 amoxicillin/clavulanic acid, 20 ceftriaxone). Among patients without signs of gravity (tachycardia, tachypnea, hypotension), 1 in every 2 received levofloxacin associated with ceftriaxone, although this combination is only for intensive care patients according to the French Society of Infectious Diseases. The mean duration of treatment was 10 days. In 1 in every 2 cases, dosage was too high according to the renal function. As a result, the exposure to levofloxacin was 49 DDD per 1000 PD in acute-care units, and 37 DDD per 1000 PD in skilled units. These results are 4 to 7 times higher than those recorded in the "RAISIN" network. For 20% of the patients, levofloxacin was ineffective and another line of antibiotic was prescribed. Conclusions: Our results suggest that to reduce exposure to fluoroquinolones we should avoid systematic association with ceftriaxone, prescribe levofloxacin as the second line after amoxicillin/clavulanic acid and reduce dose and duration. No conflict of interest.